2023
DOI: 10.3389/fendo.2022.1044673
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacteriome, mycobiome and virome alterations in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic destructive autoimmune disease of the joints which causes significant pain, functional disability, and mortality. Although aberrant immune cell activation induced by the imbalance between T helper Th1/Th17 and Treg cells is implicated in the RA development, its etiopathogenesis remains unclear. The presence of mucosal inflammation and systemic IgA-isotype-autoantibodies (anti-citrullinated peptide antibodies and rheumatoid factor) in pre-clinical RA supports the mucosal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 91 publications
(96 reference statements)
3
10
0
Order By: Relevance
“…However, due to the changes in DC activity and distribution, RA and other autoimmune diseases can also result in autoimmune inflammation [ 28 ]. Changes in DCs are thought to be the primary cause of RA, increasing DC migration to the inflamed joint [ 29 ]. The upregulation of CCR6, a chemokine CCL20 receptor on DCs, is assumed to be the source of DC attraction to synovial tissue [ 30 ].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…However, due to the changes in DC activity and distribution, RA and other autoimmune diseases can also result in autoimmune inflammation [ 28 ]. Changes in DCs are thought to be the primary cause of RA, increasing DC migration to the inflamed joint [ 29 ]. The upregulation of CCR6, a chemokine CCL20 receptor on DCs, is assumed to be the source of DC attraction to synovial tissue [ 30 ].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Not only is IL-18 linked to autoimmune diseases such as T1D and SLE, IL-18 has also been shown to play a key role in the maintenance of the intestinal epithelial barrier and regulation gut microbiota composition ( 63 , 64 ). Dysbiosis of gut microbiota has been suggested as a risk factor for the development of autoimmunity ( 65 , 66 ).…”
Section: The Roles Of Il-1β and Il-18 In Inflammationmentioning
confidence: 99%
“…Based on the research of Liang et al, fecal comparative analysis of RA patients and healthy people indicated that the contents of Flavobacterium , Eisenbergia , Escherichia coli , and Klebsiella in the feces of RA patients were higher, while the contents of Enterococcus , Pseudomonas , and Fusobacterium in the feces of healthy individuals were higher ( Liang et al, 2023 ). According to some studies, fecal samples from RA patients were analyzed and showed an increase in Wallemia and Candida species abundance, while Trichosporon , Scedosporium , and Pholiota species abundance decreased, which further indicated that the difference in the fungal microbiome might contribute to the inflammatory reaction in RA patients ( Dagar et al, 2022 ). According to other studies, Lactobacilli was related to the onset of OA, which also could be diagnosed and treated through Lactobacilli ( Marchese et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%